Implementasi Kurikulum Merdeka dalam Meningkatkan Kualitas Pembelajaran di Indonesia: Tantangan dan Strategi Adaptasi Pendidikan Abad 21 - Ekrita Yanova; Iswantir M (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research aims to analyze the implementation of the Independent Curriculum in educational units, identify the main challenges faced, and formulate relevant adaptation strategies, especially from an Islamic Education Management perspective. The method used is a systematic literature review (SLR) of scientific publications for the 2020–2025 period obtained through reputable national and international databases. The SLR process is carried out through the stages of identification, screening, eligibility and inclusion of articles based on predetermined criteria, with data analysis using a thematic synthesis approach to group findings into aspects of implementation, challenges and adaptation strategies. The results of the study show that the Merdeka Curriculum has been widely adopted, with more than 80% of schools in Indonesia implementing it in the 2023/2024 academic year. However, this study also identified structural challenges in the form of teacher competency gaps, limited digital infrastructure in 3T areas, as well as the need for a change in school leadership paradigm. From an Islamic Education Management perspective, these findings show opportunities for integrating character strengthening based on Islamic values ​​within the Independent Curriculum framework in a more contextual and sustainable manner.